Pain and pain management experiences following spinal cord injury – a mixed methods study of Australian community-dwelling adults. Issue 3 (30th January 2023) - Karran, Emma L.; Fryer, Caroline E.; Middleton, James W.; Moseley, G. Lorimer
Abstract: Purpose: There is a high prevalence of persistent pain following SCI yet insights into its impact and the quality of pain care are limited. We aimed to explore, in-depth, the problem of persistent pain in Australian community-dwelling adults with a spinal cord injury (SCI). Our objectives were to investigate (i) how individuals experience persistent pain, (ii) how they experience pain care and (iii) the concordance between clinical practice guidelines for managing pain and reported care practices. Methods: We conducted a mixed-methods convergent parallel study. Adults with SCI and persistent pain completed a survey ( n = 43); a subset of participants completed interviews ( n = 10). We analysed the data from each method separately and then integrated the findings. Results: Results indicated that the life impact of persistent pain is variable but it can be more disabling than physical impairments and compound a sense of isolation and despair. Community-based management was reported to predominantly have a pharmacological focus, with occurrences of opioid misuse apparent in the data. Access to expert, comprehensive and individualised care was frequently reported as inadequate. Conclusion: While some people with SCI and persistent pain can effectively self-manage their pain, for others the impact on quality of life is profound and complex care needs are commonly unmet. IMPLICATIONS FOR REHABILITATION: Persistent pain is a common consequence of SCI and profoundly impacts quality of life. Complex pain care needs are commonly unmet. Individuals require regular, comprehensive, biopsychosocial assessment. The effectiveness of pain management strategies must be monitored on an ongoing basis. Opportunities for personal self-management support must be available long-term.